THE USE OF DATA AGGREGATION IN MOBILE SENSOR NETWORKS - M. A. Smolnikov; Y. A. Skudnyakov (Informatika)
In the article the comparison of traditional routing algorithms with content based routing algorithms is performed. Investigation of source and sink locations influence on energy consumption, delays and data transfer reliability is made as well. It is proved, that this kind of routing may increase the efficiency of sensor networks operating in a large range of conditions.